Pelatihan Keuangan Desa Di Molalahu Kecamatan Pulubala Kabupaten Gorontalo - Yulia Puspitasari Gobel (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities in the village of Molalahu have the objectives of (1) improving the quality of human resources (village apparatus) in financial management of the village of Molalahu, (2) increasing the discipline of village government officials who occupy existing institutions. (3) Maximizing the ability of village officials in terms of processing available data, (4) improving the work pattern of village officials so that they are orderly in administration and in reporting. The method used in solving the problem is using the village management training method. The speaker of the resource training was a lecturer from IAIN Sultan Amai Gorontalo with the training participants being all apparatus from the village of Molalahu, Pulubala District, Gorontalo Regency. The outputs of this community service activity are, among others, (1) Providing excellent service, (2) Utilization of available village financial applications so that it can facilitate village officials in managing Molalahu Village finances, (3) Realization of good service in the village in accordance with regulations legislation on village financial management. The outcome of this activity is a joint commitment between village officials and village communities in realizing Good Governance through effective and efficient village financial management.